2011
DOI: 10.1016/j.vetimm.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

FIV diversity: FIVPle subtype composition may influence disease outcome in African lions

Abstract: Feline immunodeficiency virus (FIV) infects domestic cats and at least 20 additional species of non-domestic felids throughout the world. Strains specific to domestic cat (FIVFca) produce AIDS-like disease progression, sequelae and pathology providing an informative model for HIV infection in humans. Less is known about the immunological and pathological influence of FIV in other felid species although multiple distinct strains of FIV circulate in natural populations. As in HIV-1 and HIV-2, multiple diverse cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 55 publications
(83 reference statements)
1
37
0
Order By: Relevance
“…For example, Troyer et al . () identified two subtypes circulating in high frequencies within the Serengeti lion population, namely subtype B (high prevalence; 69%) and subtype C (high prevalence; 57%), whereas a third subtype was only identified in low frequencies, namely subtype A (low prevalence; 12%) (Troyer et al ., ). In contrast, we only identified one dominant subtype within the KNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Troyer et al . () identified two subtypes circulating in high frequencies within the Serengeti lion population, namely subtype B (high prevalence; 69%) and subtype C (high prevalence; 57%), whereas a third subtype was only identified in low frequencies, namely subtype A (low prevalence; 12%) (Troyer et al ., ). In contrast, we only identified one dominant subtype within the KNP.…”
Section: Discussionmentioning
confidence: 99%
“…FIV Ple subtype D (South African isolate) accounts for 87% of FIV infections within KNP, with subtypes A (6%) and E (7%) occurring in much lower frequencies. Differences in subtype frequencies could be linked to different modes of transmission (Troyer et al ., ) with vertical transmission of subtype D accounting for the high prevalence of this subtype and horizontal transmission of subtypes A and E responsible for the low prevalence of these subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular phylogenetic methods are hampered by the problem of saturation(Duchêne et al, 2015). Although no New World monkeys are known to be infected with PIVs, felines around the world are infected with feline immunodeficiency viruses with no greater diversity than is found in the African PIVs(Troyer et al, 2011)(O’Brien et al, 2012). Endogenous lentiviruses have been found in lemurs, rabbits, ferrets and weasels and estimated to have become endogenous as much as ten million years ago(Han and Worobey, 2012).…”
Section: Piv Details and Peculiaritiesmentioning
confidence: 99%
“…Historically, FIV-Ple has not been considered a cause of clinical disease in lions; however, recent research suggests FIV-Ple could be contributing to a loss of immune competence, and some subtypes of FIV-Ple are possibly more pathogenic than others (Pecon-Slattery et al 2008;Roelke et al 2009;Troyer et al 2011;O'Brien et al 2012). Further, during the 1994 Serengeti CDV outbreak, lions infected with FIV-Ple subtype B were twice as likely to survive compared to lions infected with subtypes A or C (Troyer et al 2011). Future studies should investigate the strain of FIV-Ple found in freeranging lions, and other felids, and the possible impacts these strains have on their health.…”
Section: Discussionmentioning
confidence: 99%